2014
DOI: 10.1016/j.annepidem.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and their relationship with endogenous reproductive hormones and sporadic anovulation in premenopausal women

Abstract: Purpose To determine whether depressive symptoms are associated with ovulation or reproductive hormone concentrations in eumenorrheic women without a reported diagnosis of clinical depression. Methods A prospective cohort of 248 regularly-menstruating women, aged 18–44 years (27.3± 8.2) were evaluated for depressive symptoms at baseline using the 20-item Center for Epidemiological Studies Depression (CES-D) scale and categorized dichotomously (< 16, no depressive symptoms [92%] vs. ≥16, depressive symptoms [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In a large study of 248 adult, premenopausal women (60% White), depressive symptoms and hormone levels were measured across at least two menstrual cycles. 71 The authors found no relationship between depressive symptoms and absolute levels of hormonal changes across the menstrual cycle, although women with more depressive symptoms also had worse premenstrual mood changes. Premenstrual mood worsening was also found in an earlier study, 59 and healthy women have reported higher symptoms of depression in both early and late follicular phases compared to the mid-luteal phase.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In a large study of 248 adult, premenopausal women (60% White), depressive symptoms and hormone levels were measured across at least two menstrual cycles. 71 The authors found no relationship between depressive symptoms and absolute levels of hormonal changes across the menstrual cycle, although women with more depressive symptoms also had worse premenstrual mood changes. Premenstrual mood worsening was also found in an earlier study, 59 and healthy women have reported higher symptoms of depression in both early and late follicular phases compared to the mid-luteal phase.…”
Section: Resultsmentioning
confidence: 93%
“…Epidemiological and self-report studies assessing depressive symptoms in healthy women produced inconsistent findings. In a large study of 248 adult, premenopausal women (60% White), depressive symptoms and hormone levels were measured across at least two menstrual cycles 71 . The authors found no relationship between depressive symptoms and absolute levels of hormonal changes across the menstrual cycle, although women with more depressive symptoms also had worse premenstrual mood changes.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were asked to measure their frequencies of 20 depressive feelings and behaviors in the past week with responses ranging from "rarely or none of the time" (0 points) to "most or all the time" (3 points). Each participant was given an overall score (range: 0-60) (23). At the end of the follow-up period, the total percentage of body fat was measured with the use of dualenergy X-ray absorptiometry (Hologic Discovery Elite, software version 12.4.1; Hologic Inc.).…”
Section: Covariate Assessmentmentioning
confidence: 99%
“…Available information is even more scarce on the potential link between circulating gonadotropins and depression. In one available study depressive symptoms were not associated with circulating gonadotropins in regularly menstruating women [36]. On the other hand, women aged 36 to 45 years with a history of lifetime depression had higher levels of serum LH and FSH and lower levels of oestradiol [37].…”
Section: Discussionmentioning
confidence: 84%